2019
DOI: 10.2337/cd18-0056
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diabetes Control Through Remote Glucose Monitoring in a Diabetes Self-Management Program for Employees of a Health System

Abstract: IN BRIEF This study investigates the combination of diabetes education, telehealth, a wireless enabled meter, and medication algorithms to improve care for a targeted population of employees with type 1 or type 2 diabetes. After more than 2 years of follow-up, mean A1C was reduced by 1.8%, and a reduction was observed in cost of care, along with an increase in visits with the managing physician provider. Thus, this study showed improved diabetes control using new technologies to provide remote monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…The findings of the paper are in accordance with those of Jaana and Paré [38] and others [10][11][12][13], suggesting that patients and providers will need to demonstrate continued ongoing compliance and favorable medical and economic results before these programs will be funded on a widespread basis for long-term care. Moreover, as Klonoff [39] points out, telemedicine systems are hindered by technical and structural problems that are being corrected gradually and will likely be solved in the near future.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The findings of the paper are in accordance with those of Jaana and Paré [38] and others [10][11][12][13], suggesting that patients and providers will need to demonstrate continued ongoing compliance and favorable medical and economic results before these programs will be funded on a widespread basis for long-term care. Moreover, as Klonoff [39] points out, telemedicine systems are hindered by technical and structural problems that are being corrected gradually and will likely be solved in the near future.…”
Section: Discussionsupporting
confidence: 82%
“…Many research initiatives and projects have confirmed that telehealth can support the effective and efficient application of continuity of care in diabetes [8][9][10][11][12]. Crossen, Raymond and Neinstein [13] proposed 10 steps for successfully implementing a diabetes telehealth program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least every 2–4 weeks, they contacted each patient by telephone, message, e-mail, instrument information and sent diabetes education knowledge. After two years of follow-up, mean HbA1C was reduced by 1.8%, and patients’ diabetes knowledge, self-management and self-monitoring were improved [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have demonstrated effectiveness of provider-and nurse-initiated monitoring interventions that aim to increase patients' self-care, which has resulted in positive outcomes, including decreased HbA 1c levels. [12][13][14] Interventions varied from standardized educational sessions with practical demonstrations to phone calls, texts, telehealth sessions, and technological tools. Odom et al 14 found that a combination of diabetes education, telehealth, a wireless-enabled meter, and medication algorithms reduced mean HbA 1c in diabetic patients by 1.8% and lowered the cost of care.…”
Section: Introductionmentioning
confidence: 99%